Repair Integrity in Patients Returning for an Unscheduled Visit After Arthroscopic Rotator Cuff Repair: Retorn or Not?. Issue 6 (29th May 2018) - Rizvi, Syed Mohammed Taif; Lam, Patrick; Murrell, George A.C.
Background: After rotator cuff repair, some patients have ongoing problems significant enough to warrant presentation to a clinic for reassessment. Purpose/Hypothesis: The purpose of this study was to determine whether this cohort of patients was more likely to have a healed rotator cuff. We hypothesized that patients who had an unscheduled postoperative visit were more likely to have a healed rotator cuff than those who did not have an unscheduled postoperative visit. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 321 consecutive patients who underwent arthroscopic rotator cuff repair were evaluated; of these, 50 patients had an unscheduled return to clinic that included an ultrasound assessment of the cuff repair within 4 months postoperatively. Repair integrity was evaluated in all patients at 6 months postoperatively via ultrasonography. Results: The failure-to-heal rate was greater in patients who had an unscheduled assessment (8/50; 16%) than in those who did not (14/275; 5%) ( P = .01). The patients most likely to have a repair failure were those who were assessed before 2 weeks and after 12 weeks (7/18; 39%) compared with those who were assessed between 3 and 12 weeks (1/32; 3%) ( P = .001). The failure-to-heal rate was very low in patients who had an unscheduled assessment with a tear size smaller than 4 cm 2 (0/34; 0%) compared with those with tear sizes greater than 4 cm 2 (8/16; 50%) ( P < .0001, Fisher exact text). Conclusion: Patients who had an unscheduled clinic visit after rotator cuff repair had a 16% chance of a failed healing response, whereas those who did not have an unscheduled visit had a 5% rate of failed healing. The risk of a failed healing response was greater if the tear was larger than 4 cm 2, if patients presented within 2 weeks following surgery, or if they presented after 12 weeks postsurgery.